1999
DOI: 10.1016/s0022-5347(05)68935-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Chemotherapy With Epirubicin: A Dose Response Study

Abstract: Epirubicin at double the standard dose for intravesical chemotherapy of superficial bladder cancer is not superior in regard to marker tumor response, time to first recurrence or recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Other studies did not find a difference in efficacy between different drug concentrations [31][32][33][34]36]. Weekly instillations during 5 mo appear to be as effective as long-term instillations during 3 yr, which were given less frequently during the initial 5-mo period [26,27].…”
Section: Discussionmentioning
confidence: 84%
“…Other studies did not find a difference in efficacy between different drug concentrations [31][32][33][34]36]. Weekly instillations during 5 mo appear to be as effective as long-term instillations during 3 yr, which were given less frequently during the initial 5-mo period [26,27].…”
Section: Discussionmentioning
confidence: 84%
“…Bladder instillations, active against urothelial tumours, could have considerable advantages: no need for anesthesia, no wounds at the bladder mucosa, chemoresection of small, still invisible tumours and no implantation. Studies on upfront use instillations in order to avoid TURB are scarce [8,16], but uniformly demonstrate that it is a good solution in small papillary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Although strong evidence is lacking, optimizing the pH by dissolving the MMC in phosphate buffer and reducing drinking before the instillation may be useful. There is one study [16] in 100 patients with a single 50- or 100-mg ERC instillation describing complete ablation of papillary tumours in about half of the patient with both dosages. This would suggest that even a single instillation might be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study compared the recurrence rates of superficial bladder cancer for 30 mg of thiotepa mixed in 30 ml normal saline group and 40 mg of thiotepa mixed in 40 ml of normal saline, and reported that the effect of thiotepa on recurrence was determined by not total dose but by its concentration (13). On the other hand, other researchers performed a study in which they administered different concentrations (1 mg/ml or 2 mg/ ml) of epirubicin to superficial bladder cancer patients intravesically, and they reported that the effect of epirubicin was dose-dependent, because they observe similar response rates (14).…”
Section: Discussionmentioning
confidence: 99%